The influence of competition on visitor satisfaction and loyalty - Taplin, Ross (Pergamon, 2013)
Using visitor survey results from a metropolitan zoo, this paper shows how measuring satisfaction and loyalty relative to competitors results in different and more easily interpretable measures to those currently considered in the literature. These new measures possess distributions with reduced skewness and increased variability, reducing a problem that has plagued visitor studies. Furthermore, loyalty can be predicted more successfully by attribute performance when both are measured relative to competitors, providing stronger convergent validity for loyalty when this is measured relative to competitors explicitly. Benchmarking satisfaction and loyalty to competitors provides improved tools for management and new avenues for tourism and consumer research.